Turning a Negative into a Positive: Ascending GABAergic Control of Cortical Activation and Arousal - Brown, Ritchie E.; McKenna, James T. (Frontiers in Neurology, 2015)
Gamma-aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the brain. Recent technological advances have illuminated the role of GABAergic neurons in control of cortical arousal and sleep. Sleep-promoting GABAergic neurons in the preoptic hypothalamus are well-known. Less well appreciated are GABAergic projection neurons in the brainstem, midbrain, hypothalamus and basal forebrain which paradoxically promote arousal and fast electroencephalographic (EEG) rhythms. Thus, GABA is not purely a sleep-promoting neurotransmitter. GABAergic projection neurons in the brainstem nucleus incertus and ventral tegmental nucleus of Gudden promote theta (4-8 Hz) rhythms. Ventral tegmental area GABAergic neurons, neighboring midbrain dopamine neurons, project to the frontal cortex and nucleus accumbens. They discharge faster during cortical arousal, and regulate reward. Thalamic reticular nucleus GABAergic neurons initiate sleep spindles in non-REM sleep. In addition, however, during wakefulness they tonically regulate the activity of thalamocortical neurons. Other GABAergic inputs to the thalamus arising in the globus pallidus pars interna, substantia nigra pars reticulata, zona incerta and basal forebrain regulate motor activity, arousal, attention and sensory transmission. Several subpopulations of cortically-projecting GABAergic neurons in the basal forebrain project to the thalamus and neocortex and preferentially promote cortical gamma-band (30-80 Hz) activity and wakefulness. Unlike sleep-active GABAergic neurons, these ascending GABAergic neurons are fast-firing neurons which disinhibit and synchronize the activity of their forebrain targets, promoting the fast EEG rhythms typical of conscious states. They are prominent targets of GABAergic hypnotic agents. Understanding the properties of ascending GABAergic neurons may lead to novel treatments for diseases involving disorders of cortical activation and wakefulness.